Assessment of chromium contamination in the Monte Alegre stream: a case study - Corbi, Juliano José; Santos, Felipe André dos; Zerlin, Ricardo; Santos, Ademir dos [UNESP]; Froehlich, Claudio Gilberto; Trivinho-Strixino, Susana (Brazilian Archives of Biology and Technology, 2011)
The aim of this work was to study the contamination by chromium in the sediments of the Monte Alegre stream and in the larvae of Odonata and the possible impact caused by them on the stream macroinvertebrates community. It was found that chromium contaminated the sediments and the aquatic biota. Although, the stream macroinvertebrates community structure did not appear to be modified.
Keywords: stream macroinvertebrates; contamination; chromium